Possible Role of Interleukin-6 in PC12 Cell Death Induced by MPP+ and Tetrahydroisoquinoline - Naoko Shimma; Nobuteru Akiyama; Michiko Umezawa; Yasunobu Okuma; Yasuyuki Nomura; Takeshi Saito; Syunji Horie; Toshihiko Murayama (Elsevier, 2003)
ABSTRACT: Interleukin (IL)-6 has been shown to protect neuronal cells from cell death induced by various stimulants. Although neuronal cells including PC12 cells were shown to produce IL-6, little is known about the effects of dopaminergic neurotoxins, 1,2,3,4-tetrahydroisoquinoline (TIQ) and 1-methyl-4-phenylpyridinium ion (MPP+), on IL-6 expression in PC12 cells. In the present study, we investigated the role of IL-6 in the TIQ- and MPP+-induced cell death in PC12 cells. Treatment with 3.2 mM TIQ for 24 h caused a delayed cell death (lactate dehydrogenase (LDH) leakage and nuclear DNA fragmentation) markedly 72 h after the addition. Addition of 0.4 mM MPP+ caused LDH leakage and nuclear DNA fragmentation 24 h after the addition. The cell death induced by MPP+ was inhibited by an inhibitor of caspases, z-Val-Ala-Asp(OMe)-fluoromethylketone. The cell death induced by TIQ or MPP+ was inhibited by nerve growth factor and 10% serum and significantly enhanced by the treatment with anti-IL-6 antibody. Both neurotoxins decreased the IL-6 mRNA level in PC12 cells without changing the other tested mRNA levels (IL-1α, β-actin, etc.). These findings suggest that dopaminergic neurotoxins cause cell death in PC12 cells at least partially by changing IL-6 expression.